(untitled) (International Journal of Ayurveda and Pharma Research, 2018)
Introduction: Gridhrasi is a condition characterized by Ruk, Toda, Stambha, Spandana in Sphik pradesha and radiates downwards to Kati, Prusta, Uru, Janu, Jangha and Pada. Gridhrasi can be compared with Sciatica. Siravyadhais the major line of treatment mentioned in Ayurveda classical texts. Case study: A female patient aged 35 years; presenting with cardinal clinical signs and symptoms of Gridhrasi visited OPD with history of eight years and worsen in last two days. She was examined thoroughly and detailed history of illness was recorded. She was treated with Siravyadha atantara kandara gulpha sandhi by following proper Purva, Pradhana and Paschyat karma. Observation and Result: patient got relief in subjective parameters i.e. Ruk and Stambha. There was marked improvement in SLR test, mild improvement in Rt. Lateral Flexion and Backward extension of lumbar spine Movement. Forward Flexion and Lt. Lateral flexion of lumbar spine Movement remained unchanged. Conclusion: Siravyadha is administered in Tridoshadushti and Sarvangagatadushti. In Ghridrasi, Rakta and Kandara are Dushya and Vyana vata is major Dosha. Siravyadha corrects these imbalances by letting out the vitiated blood. The procedure was simple, economical and can be done in OPD level. It gives immediate relief of pain and stiffness.